2019
DOI: 10.1016/j.compcom.2019.102522
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Writing Composition Among CFL Learners: A Comparison Between Handwriting and Typewriting

Abstract: Situated in the context of CFL (Chinese as a foreign language), the current study examines and compares texts produced by twelve pre-intermediate CFL learners using both pen-and-paper and the pinyin input system. The participants were also invited for interviews to investigate their attitudes towards handwriting and typewriting. Because of the ease of use of the pinyin input system, CFL learners tend to prefer it over writing by hand when composing lengthy texts. Based on the evaluations of fifteen professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…They expressed that typing benefited their higher‐order thinking while composing longer texts. Overall, learners in Zhang and Min's (2019) study reported no strong preference for either mode when completing writing tasks in Chinese.…”
Section: Literature Reviewmentioning
confidence: 87%
See 1 more Smart Citation
“…They expressed that typing benefited their higher‐order thinking while composing longer texts. Overall, learners in Zhang and Min's (2019) study reported no strong preference for either mode when completing writing tasks in Chinese.…”
Section: Literature Reviewmentioning
confidence: 87%
“…Li and Zhang (2016) argued that typing reduces learners' burden to simpler tasks of phonetic spelling and recognition and that it allows the synchronization of oral language and literacy development among students. A recent study by Zhang and Min (2019) reported that their student participants perceived the handwriting of characters helpful in improving their reading proficiency, but considered it time‐consuming. They expressed that typing benefited their higher‐order thinking while composing longer texts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang & Reilly, 2015), it has been suggested that typing with input software be introduced, in order to equip CFL learners with the ability to communicate in contemporary life (Q. Zhang & Min, 2019;Zhu, Shum, Tse, & Liu, 2016). The ease of typing Chinese may help writing skills catch up with oral skills.…”
Section: Previous Textbook Research: Cfl and Other Foreign Languagesmentioning
confidence: 99%
“…However, online teaching means pedagogical practice has to rely on digital input rather than pen and paper, which minimises the opportunities for handwriting. One of the main input methods -indeed, the most popular in China -is pinyin input (Zhang & Min, 2019;Zhou et al, 2020). This requires knowledge of the sound of the Chinese characters, as pinyin is the system of romanising character pronunciation.…”
Section: Teaching Chinese Characters Online: the Status Quomentioning
confidence: 99%
“…On the other hand, behavioural research and neuroimaging studies reveal that heavy reliance on pinyin may hinder reading development or even child brain development (Tan et al, 2013;Zhou et al, 2020). Moreover, recent studies (Zhang & Min, 2019;Zhu et al, 2016) suggest that CFL learners may Qi Zhang benefit from typing with an input method if it were introduced at the intermediate level, rather than to complete beginners. It is therefore challenging to teach Chinese characters to CFL beginners online, where handwriting is unlikely to happen.…”
Section: Teaching Chinese Characters Online: the Status Quomentioning
confidence: 99%